PERSEPSI LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK MINUMAN BERENERGI - Aris Setyawan Prima Sandi; Marsudi .; Dedy Rahmawanto (Universitas muhammadiyah malang, 2011)
Universitas Muhammadiyah MalangE-mail: aris.estyawan99@gmail.com, marsudi@umm.ac.id, dedi@umm.ac.idABSTRACTThe aim of this research is to know the influence of consumer’s perception of Halal label at energybeverage product on purchasing decision. Then it is also to know the correlation of consumer’s perceptionof Halal label. Analyses method used multiple linier regression. Consumer’s perception variablesinclude attention, understanding and memory. The result of analysis show that consumer’s perception(attention, understanding and memory) of Halal label simultaneously influence to decision of purchasingon energy beverage product. There are two independent variables partially significant influence todecision of purchasing. Two variables are attention and memory. The correlation coefficient for attention,understanding and memory variables with decision of purchasing variable is in strong level. Itexemplified those attention, understanding and memory variables are very strong correlation to decisionof purchasing.Keywords: perception, halal label, decision of purchasing